The search - Korman, Gordon (New York : Scholastic, 2006)
Aiden works with the FBI in order to rescue his sister Meg, who was kidnapped.
"An Apple paperback."
Grade level: 9-12.
750
Accelerated Reader AR
Keywords: Kidnapping -- Juvenile fiction; Brothers and sisters -- Juvenile fiction